Timing and Spectral Evolution of the Magnetar 1E 1841-045 in Outburst - George Younes; Samuel K. Lander; Matthew G. Baring; Marlon L. Bause; Rachael Stewart; Zaven Arzoumanian; Hoa Dinh Thi; Teruaki Enoto; Keith C. Gendreau; Tolga Güver; Alice K. Harding; Wynn C. G. Ho; et al. (The Astrophysical Journal)
We present timing and spectral analyses of Neutron star Interior Composition Explorer (NICER), Nuclear Spectroscopic Telescope Array (NuSTAR), and IXPE observations of the magnetar 1E 1841−045 covering 82 days following its 2024 August bursting activity as well as radio observations utilizing MeerKAT and Effelsberg. We supplement our study with a historical NuSTAR observation and all 2024 preoutburst NICER observations. The outburst is marked by an X-ray flux enhancement of a factor of 1.6 compared to the historical level, predominantly driven by a newly formed nonthermal emitting component with a photon index Γ = 1.5. This flux showed a 20% decay at the end of our monitoring campaign. The radio monitoring did not reveal any pulsed radio emission with an upper limit of 20 mJy and 50 mJy ms on the mean flux density and single pulse fluence, respectively. We detect a spin-up glitch at outburst onset with Δ ν = 6.1 × 10 ^−8 Hz and ${\rm{Δ }}\dot{ν }=-1.4× 1{0}^{-14}$ Hz s ^−1 , consistent with the near universality of this behavior among the continuously monitored magnetars. Most intriguingly, the 1E 1841−045 2–10 keV pulse profile is markedly different compared to preoutburst: it shows a new, narrow (0.1 cycle) peak that appears to shift toward merging with the main, persistently present, pulse. This is the second case of pulse-peak migration observed in magnetars after SGR 1830−0645, and the two sources exhibit a similar rate of phase shift. This implies that this phenomenon is not unique and might present itself in the broader population. The newly formed peak for 1E 1841−045 is nonthermal, with emission extending to ≳20 keV, in contrast to the case of SGR 1830−0645. Our results are consistent with an untwisting magnetic field bundle with migration toward the magnetic pole, perhaps accompanied by plastic motion of the crust.